The Problem Of Spiritual Balance Of Human In The Rubaiyat Of Bahauddin Naqshband - Navruzova, Gulchehra Nigmatovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article philosophically analyzes the importance of the ideas of repentance, forgiveness and the virtues of atonement for bringing a person to spiritual balance by the founder of the teaching of Naqshbandiya Bahauddin Naqshband, based on the rubaiyat of the book “Ruboiyoti Khoja Naqshband”, which is still unknown to the public.